Proximate Analysis of Mud Crab (Scylla serrata) powder - Surya Kanta Chanda; Kartick Boxi; Soumyadev Manna; Ranajit Kumar Khalua (The Bioscan, 2024)
The mud crab, Scylla serrata, is an important species in aquaculture and fisheries, particularly in tropical and subtropical regions. This study aims to conduct a proximate analysis of S. serrata to determine its nutritional composition, which is crucial for understanding its dietary value and potential for aquaculture. The proximate analysis includes the determination of moisture, protein, lipid, ash, and carbohydrate content. Results indicate that S. serrata is a valuable source of protein and essential fatty acids, highlighting the species' importance in human nutrition and aquaculture.